Persepsi pekerja terhadap faktor-faktor perkembangan kerjaya : kajian kes di perbadanan perbekalan lektrik Sarawak - Dayang Norlila, bt. Awang Dolhan. (Universiti Malaysia Sarawak (UNIMAS), 2001)
This study aims to detennine the perception of non-executive employees towards the career development in Sarawak Electricity Supply Corporation (SESCo). This study also examines the rel4tionship between the factors ofcareer development and employee's perception towards the career developmenJ. They were two variables in this study, namely the dependent variable (employee's perception towards the career development) and the independent variables (Training, Transfer, Evaluation System, Job Enrichment and Education. 45 respondents from SESCo were selected by /ISing the simple random sampling. The data was collected using a standard questionnaire and tested /ISing the statistical analysis such as Pearson Correlation 'r' and T-test. The findings showed that with the T-test, the selected demography (education) have significant relationship towards the employee's perception (t = -0.995 and P =0.423). With the Pearson Correlation analysis, findings showed that all factors are significant and positive with the perception of non-executive employees. The entire findings were Training (r = 0.568, p < 0.01), Transfer (r = 0.781, p < 0.01), Job Enrichment (r =0.773, p < 0.01), and Evaluation System (r = 0.618, p < 0.01). 1t is suggested that future researchers do a more research in depth in with the relevant and suitable factor used in career tkvelopment and include all the perception ofthe worker's in the SESCo.